Tobacco Use Is Associated With Increased 90-Day Readmission Among Patients Undergoing Surgery for Degenerative Spine Disease. Issue 5 (June 2022) - Connor, Michelle; Briggs, Robert G.; Bonney, Phillip A.; Lamorie-Foote, Krista; Shkirkova, Kristina; Min, Elliot; Ding, Li; Mack, William J.; Attenello, Frank J.; Liu, John C.
Study Design: Retrospective database study. Objective: Tobacco use is associated with complications after surgical procedures, including poor wound healing, surgical site infections, and cardiovascular events. We used the Nationwide Readmissions Database (NRD) to determine if tobacco use is associated with increased 30- and 90-day readmission among patients undergoing surgery for degenerative spine disorders. Methods: Patients who underwent elective spine surgery were identified in the NRD from 2010 to 2014. The study population included patients with degenerative spine disorders treated with discectomy, fusion, or decompression. Descriptive and multivariate logistic regression analyses were performed to identify patient and hospital factors associated with 30- and 90-day readmission, with significance set at P value <.001. Results: Within 30 days, 4.8% of patients were readmitted at a median time of 9 days. The most common reasons for 30-day readmission were postoperative infection (12.5%), septicemia (3.5%), and postoperative pain (3.0%). Within 90 days, 7.3% were readmitted at a median time of 18 days. The most common reasons for 90-day readmission were postoperative infection (9.6%), septicemia (3.5%), and pneumonia (2.3%). After adjustment for patient and hospital characteristics, tobacco use was independently associated with readmission at 90 days (odds ratio 1.05, 95% confidence interval 1.03-1.07, P < .0001) but not 30 days (odds ratio 1.02, 95% confidence interval 1.00-1.05, P = .045). Conclusions: Tobacco use is associated with readmission within 90 days after cervical and thoracolumbar spine surgery for degenerative disease. Tobacco use is a known risk factor for adverse health events and therefore should be considered when selecting patients for spine surgery.